Interrelationships of contextual factors, personal factors and gaming behaviour among adolescents in Malaysia - Fam, Jia Yuin (2021)
The inclusion of Internet Gaming Disorder as a potential psychiatric condition in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders had invited much research on problematic gaming behaviour. Past studies had consistently highlighted the significant role of parent-adolescent relationship in predicting problematic gaming behaviour among adolescents. However, other contextual factors and personal factors were not taken into account. Hence, it is the aim of this study to (i) describe contextual factors (mother-adolescent relationship, father-adolescent relationship, school engagement, and peer relationship), personal factors (gaming self-esteem beliefs, time spent gaming, and gaming motives), and problematic gaming behaviour among adolescents, (ii) determine the relationships between contextual factors, personal factors, and problematic gaming behaviour of the respondents, (iii) determine the factors that uniquely predict problematic gaming behaviour among the respondents, and (iv) examine whether the relationships between contextual, personal factors, and problematic gaming behaviour are mediated by gaming motives. A total of 710 adolescents were invited to participate in the current study. The final sample consists of 595 adolescents aged between 12 and 18 years old (mean = 15.36, SD = 1.27). They were located in four districts in Selangor, namely Gombak, Hulu Langat, Klang, and Petaling Perdana. The respondents were requested to complete a set of self-report questionnaire, which include respondents’ background, Problem Videogame Playing Scale (Tejeiro & Bersabé, 2002), the revisited version of Inventory for Parent and Peer (Armsden & Greenberg, 1987), School Engagement Scale (Fredricks et al., 2005), Index of Peer Relation Scale (Hudson et al., 1990), Gaming Self-Esteem Beliefs Subscale from the Internet Gaming Cognition Scale (King & Delfabbro, 2016), and Online Gaming Motivation Scale (Yee et al., 2012). Following the recommendation by Jackson et al. (2009), all hypothesized models were tested using chi-square (χ2), non-normed fit index (TLI), comparative fit index (CFI), root mean square error of estimation (RMSEA), and relative chisquare (χ2/df). Descriptive analysis revealed that more than half of the adolescents reported moderate level of mother-adolescent relationship, moderate level of fatheradolescent relationship, moderate level of peer relationship, moderate level of school engagement, moderate level of gaming self-esteem beliefs, moderate level of gaming motives, and low level of problematic gaming behaviour. Pearson correlation analysis revealed that mother-adolescent relationship, father-adolescent relationship, peer relationship, gaming self-esteem beliefs, time spent gaming, and gaming motives significantly correlate with problematic gaming behaviour, but no significant relationship was found between school engagement and problematic gaming behaviour. However, mother-adolescent relationship, father-adolescent relationship, school engagement, and peer relationship did not significantly predict problematic gaming behaviour when all variables were simultaneously accounted for. Structural equation modelling revealed gaming motives fully mediates the relationship between school engagement and problematic gaming behaviour. Additionally, gaming motives also partially mediate the relationship between gaming self-esteem beliefs, time spent gaming, and problematic gaming behaviour. The current finding highlights the significant role of gaming motives in predicting problematic gaming behaviour among adolescents. Contrary to the traditional compulsive view of problematic gaming behaviour, the current study suggests that adolescents play games for a reason. More precisely, adolescents who engage in school, reported high gaming self-esteem beliefs, and spent longer time playing games are motivated to play games. Practically, parents, educators, and social workers should be aware that adolescents are being motivated to play games.